Manganese-based composite zirconium tungsten oxide denitration catalyst as well as preparation method and application thereof

By using manganese-based composite zirconium tungsten oxide catalyst in SCR catalyst, and using the synergistic effects of Zr, W and Mn, the existing catalysts have narrow working temperature windows and poor stability under low temperature conditions, and efficient NOx conversion in the range of 120-320℃ is achieved, which is suitable for a variety of industrial applications.

CN119746844AActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411807388.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing SCR catalysts have narrow working temperature windows and poor stability under low temperature conditions, which cannot meet the needs of low processing temperatures in the industry.

Method used

Manganese-based composite zirconium tungsten oxide denitrification catalyst is used to improve the low-temperature catalytic conversion capacity of the catalyst and broaden the working temperature window through the synergistic effect between Zr, W and Mn. The catalyst was obtained by heat treatment of ZraWb-MnO2 precursor at 300-500°C under an air atmosphere and prepared by hydrothermal reaction and calcination steps.

Benefits of technology

Within the temperature range of 120-320℃, the NOx conversion rate of the catalyst remains above 90%, and reaches 100% conversion rate at 160℃, and has good reaction stability. It is suitable for application scenarios with low processing temperatures such as steel plants and cement plants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746844A_ABST
    Figure CN119746844A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese-based composite zirconium tungsten oxide denitration catalyst as well as a preparation method and application thereof. The catalyst is obtained by carrying out heat treatment on a ZraWb-MnO2 precursor in an air atmosphere at the temperature of 300 to 500 DEG C; the ZraWb-MnO2 precursor is prepared by the following steps: adding soluble manganese salt and ammonium persulfate into a solvent, dissolving, mixing, stirring to be transparent, adding soluble zirconium salt and soluble tungsten salt, stirring, dissolving, transferring into a reaction kettle, carrying out hydrothermal reaction at 80-120 DEG C for 5-50 hours, taking out, cooling to room temperature, and filtering, washing and drying the obtained solid-liquid mixture to obtain the ZraWb-MnO2 precursor. Compared with a single-component Mn-based metal oxide low-temperature catalyst, the low-temperature catalyst disclosed by the invention has the advantages that two metal elements of Zr and W are utilized to modify the active substrate MnO2, so that the low-temperature catalytic activity is effectively improved, and the overall working temperature window is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to SCR (selective catalytic reduction) flue gas denitration technology, in particular to a low-temperature SCR denitration catalyst using NH3 as a reducing agent and a preparation method and application thereof, belonging to the field of air purification technology and environmental protection catalytic materials. Background Art

[0003] Currently commonly used NO x Treatment technologies include catalytic and non-catalytic reduction, wet scrubbing in adsorption processes, photocatalysis, plasma catalysis, etc. Catalytic and non-catalytic reduction are the most widely used methods in current industrial plants. They include selective catalytic reduction (SCR) technology and selective non-catalytic reduction (SNCR) technology. Compared with SNCR technology, SCR technology has higher denitrification efficiency and requires lower reaction temperatures. The core factor is the participation of catalysts in the reaction process. Catalytic activity, N2 selectivity, high conversion rate operating temperature window, resistance to poisoning molecules such as SO2 / H2O, etc. are all important criteria for judging the quality of catalysts and are also key indicators for measuring whether they can be used in industrialization. However, traditional V2O5-WO3 / TiO2 catalysts have problems such as a narrow temperature window (300-400°C) and biological toxicity of the active component V. In application scenarios with low processing temperatures such as steel mills and cement plants, the catalytic efficiency of V2O5-based catalysts is affected by temperature and cannot meet industrial needs. On the other hand, since there are a large number of SO2, heavy metal ions and other elements that poison catalysts in industrial waste gas, the catalytic device needs to be placed after the desulfurization and dust removal device. At this time, the waste gas temperature is low. Therefore, it is necessary to develop an SCR catalyst that can efficiently catalyze conversion at low temperature.

[0004] Chinese invention patent application 202410636962.X discloses a method for preparing a modified denitrification catalyst loaded with manganese and cerium on modified biochar and its application. This technology uses a strong acid to modify the surface of biochar, and then loads three metal salts of manganese acetate, cerium nitrate and iron nitrate on the modified biochar. This technology can catalyze NO at 80-240°C. x However, the temperature window for the catalyst involved in the invention to maintain a high conversion rate under low temperature conditions is narrow, especially for NO x The operating temperature window for conversion above 90% is only 80°C.

[0005] Chinese invention patent application 202210504112.5 discloses a low-temperature manganese-based catalyst, its preparation method and application. Manganese salt, cerium salt and tetraethyl silicate are introduced by co-precipitation method, calcined to obtain a composite metal oxide, and then the catalyst is acidified by inorganic acid. Some active components of the SCR catalyst developed by this invention exist on the surface in the form of metal sulfates. The acid-base-oxidation synergistic effect of sulfates and surface metal salts is utilized to increase the storage of active oxygen, effectively promote the adsorption of NH3 and NO, and increase the acidic position of the catalyst by sulfated metal salts, thereby enhancing the adsorption of NH3 at medium and high temperatures, thereby improving the medium and high temperature performance, so that the catalyst is NO in the temperature range of 110 to 260°C. x The conversion rate of 2.5 wt% was maintained at over 90%. However, the space velocity during the technology test was only 50,000 h -1 The NO concentration in the flue gas is only 500ppm, and the catalyst can reach more than 90% NO at a relatively low air velocity. x The temperature window for conversion is only 150°C, and when the catalyst NO x After the conversion rate reaches the maximum efficiency, it drops sharply as the temperature increases, indicating that the applicability of the catalyst designed in this patent is too low outside the effective temperature.

[0006] Chinese invention patent CN114308053B discloses a denitration catalyst with high entropy oxide as active component and its preparation and application. By loading high entropy oxides on TiO2, including iron nitrate, cobalt nitrate, manganese nitrate, cerium nitrate and neodymium nitrate, the gas adsorption, activation and reaction desorption process involved in the denitration reaction is based on its high entropy effect, lattice distortion effect, hysteresis diffusion effect, etc. However, the optimal active temperature window of this technology is still narrow after modification, and only NO in the temperature range of 175-275℃ is activated. x The conversion rate remains above 90%, which shows that it is difficult to apply to low temperature ranges below 150°C. In addition, the catalyst activity changes significantly in the entire temperature range, and the catalytic efficiency is easily affected by temperature, which is not suitable for mobile source exhaust gas treatment. Summary of the invention

[0007] In order to solve the problem that existing commercial catalysts have high operating temperatures and limited applicable scenarios, the present invention aims to provide a manganese-based composite zirconium tungsten oxide deNOx catalyst with high stability, excellent low-temperature catalytic activity and a wide operating temperature window, and a preparation method thereof.

[0008] Another object of the present invention is to provide the use of the manganese-based composite zirconium tungsten oxide denitration catalyst in flue gas denitration. The catalyst obtained by the present invention ensures that the catalyst efficiency remains above 90% in the temperature range of 120-320°C, reaches 100% conversion rate at 160°C, and has good reaction stability.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] Manganese-based composite zirconium-tungsten oxide denitrification catalyst, composed of Zr a W b -MnO2 precursor is obtained by heat treatment at 300-500°C in air atmosphere; the Zr a W b -MnO2 precursor is prepared by adding soluble manganese salt and ammonium persulfate into a solvent, dissolving them, mixing them, stirring until transparent, then adding soluble zirconium salt and soluble tungsten salt, stirring and dissolving, transferring them to a reactor, and hydrothermally reacting them at 80-120°C for 5-50h, taking them out and cooling them to room temperature, filtering, washing and drying the obtained solid-liquid mixture; wherein a and b represent the molar fractions of Zr and W used, respectively, and the molar ratio of Mn, Zr and W is 1:a:b, and a and b are 1%-10%.

[0011] The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst comprises the following steps:

[0012] 1) After mixing soluble manganese salt and ammonium persulfate, add solvent to dissolve, stir until transparent, then add soluble zirconium salt and soluble tungsten salt, stir to dissolve, transfer to a reactor, hydrothermally react at 80-120° C. for 5-50 hours, take out and cool to room temperature, filter, wash and dry the obtained solid-liquid mixture to obtain a solid precursor;

[0013] 2) The solid precursor obtained in step 1) is calcined at 300-500° C. to obtain a manganese-based composite zirconium-tungsten oxide denitration catalyst.

[0014] To further achieve the purpose of the present invention, preferably, the soluble manganese salt is one or more of manganese sulfate monohydrate, manganese acetate tetrahydrate, manganese nitrate tetrahydrate, manganese chloride tetrahydrate and potassium permanganate;

[0015] The soluble zirconium salt is one or more of zirconyl chloride, zirconyl nitrate and zirconium nitrate pentahydrate;

[0016] The soluble tungsten salt is ammonium metatungstate and / or ammonium tungstate.

[0017] Preferably, the molar ratio of the soluble manganese salt to the soluble zirconium salt is 1:0.01-0.1; the molar ratio of the soluble manganese salt to ammonium persulfate is 1:1-10; the molar ratio of the soluble manganese salt to the soluble tungsten salt is 1:0.0008-0.008;

[0018] The solvent is deionized water or citric acid solution; the mass ratio of the solvent to the soluble manganese salt is 1:0.03-0.06.

[0019] Preferably, the drying is carried out in a forced air drying oven or a vacuum drying oven at 60-120° C. for 4-30 hours.

[0020] Preferably, the calcination time is 1-10 hours.

[0021] The manganese-based composite zirconium-tungsten oxide denitration catalyst is used in flue gas denitration.

[0022] Preferably, the method comprises the following steps:

[0023] 1) tabletting and granulating the manganese-based composite zirconium-tungsten oxide denitration catalyst;

[0024] 2) The granulated catalyst obtained in step 1) is fixedly loaded into a fixed bed reactor through quartz wool, and the fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path; the catalyst is fixedly placed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor, and the reaction temperature is controlled by controlling the temperature of the reactor, and the flue gas is combined according to the set flow rate and then discharged through the quartz tube, and the flue gas flow rate of each 0.5g catalyst is 600-1400mL / min;

[0025] 3) The reaction temperature is controlled to be 60-320°C by a programmed temperature reactor.

[0026] Preferably, the catalyst granulation mesh size in step 1) is 40-80 mesh;

[0027] The composition of the flue gas in step 2) is as follows: the concentration ratio of NO to NH3 is 1:1-1.5, the concentration of O2 is 2.8-4.5%, and N2 is the balance gas.

[0028] Preferably, in step 3), the reaction temperature is programmed to rise from 60°C to 320°C at a rate of 1-10°C / min; and the holding time for each temperature section for data collection is 15-20 min.

[0029] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0030] 1) Compared with the single-component Mn-based metal oxide catalyst, the present invention utilizes the synergistic effect between Zr and W metals and Mn to effectively improve the low-temperature catalytic conversion ability of the catalyst and broaden the working temperature window. The test results show that the catalyst has excellent NO at low temperatures. x Conversion capacity. Under the conditions of excess oxygen content and high space velocity of 120,000 mL of flue gas treated per unit mass (gram) of catalyst per hour, the NO conversion capacity of the catalyst in the temperature range of 120-320°C x The conversion rate can be maintained above 90%, and the activity curve tends to be flat in the entire temperature range without any sudden drop.

[0031] 2) The catalyst of the present invention has strong stability. After being used for more than 12 hours and recycled three times, its activity does not decrease significantly, which is significantly better than some existing catalysts.

[0032] 3) The in-situ doping method used in the preparation process of the catalyst used in the present invention regulates the formation state of Zr and W elements on the MnO2 surface, and the better doping ratio synergistically regulates the balance between the catalyst's oxidation ability and acidity, so that the catalyst has excellent NH3-SCR performance.

[0033] 4) Compared with the operating temperature of commercial catalysts at least above 400°C, the NO x The conversion rate can be maintained above 90%, the working temperature range is lower, the temperature window is wider, and it has better low-temperature denitrification efficiency. It can be used in steel mills, cement plants and other applications with low processing temperatures. There is no need for secondary heating of exhaust gas, reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The catalysts Zr1W1-MnO2, Zr 2.5 W 2.5 -MnO2、Zr5W5-MnO2、Zr 10 W 10 -MnO2 NO x Conversion rate;

[0035] Figure 2 The catalysts Zr1W1-MnO2, Zr 2.5 W 2.5 -MnO2、Zr5W5-MnO2、Zr 10 W 10 -XRD pattern of MnO2;

[0036] Figure 3 The catalysts Zr1W1-MnO2, Zr 2.5 W 2.5 -MnO2、Zr5W5-MnO2、Zr 10 W 10 -N2 physical adsorption-desorption isotherm of MnO2.

[0037] Figure 4 The catalysts Zr1W1-MnO2, Zr 2.5 W 2.5 -MnO2、Zr5W5-MnO2、Zr 10W 10 -Pore size distribution diagram of MnO2. DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.

[0039] Mn-based catalyst is a representative low-temperature SCR catalyst. Its active center Mn is cheap and widely available. However, single Mn-based catalyst has many limitations and it is difficult to achieve low-temperature and efficient catalytic conversion of NO. x In view of this, the present invention uses MnO2 as a carrier, in-situ doping of transition metal elements with significantly different oxidizability, and changing the preparation conditions to directionally regulate the crystal form and phase of the catalyst active phase, thereby solving the current problems of narrow working temperature window and poor stability of low-temperature catalysts.

[0040] Comparative Example 1: Preparation of MnO2 metal oxide denitration catalyst, the steps are as follows:

[0041] Preparation of MnO2: Weigh 6.32g of manganese sulfate monohydrate (MnSO4·H2O) and 8.578g of ammonium persulfate ((NH4)2S2O8), add 200mL of water, stir and dissolve, and transfer to a 200mL hydrothermal kettle to react at 90°C for 24h to obtain a solid-liquid mixture. After cooling to room temperature, filter, wash, and dry in a 60°C forced air drying oven. Grind the obtained precursor into powder, transfer it to a crucible, place it in a muffle furnace and heat it to 320°C at a heating rate of 2°C / min, and keep it at a constant temperature for 4h to obtain a MnO2 metal oxide solid denitrification catalyst.

[0042] The obtained catalyst is pressed into tablets and granulated, and the granulated catalyst of 40-60 mesh is loaded into a fixed bed reactor, and the catalyst activity is evaluated by a fixed bed reaction device. The fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path. The temperature of the reactor is controlled by a program temperature rise, a K-type thermocouple detects and feeds back the temperature signal, an 8mm quartz tube is used as a reaction channel, and quartz wool is a fixed bed layer. The catalyst is fixed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor. The reaction temperature is controlled by controlling the temperature of the reactor. After the gases in each channel are adjusted by a pressure reducing valve and a flowmeter, a mixed gas is formed at a set flow rate, and then passed into a quartz tube. After the mixed gas is catalytically deoxidized by the catalyst, it is discharged, and the inlet and outlet gas concentrations are detected by an EN2-F flue gas analyzer of German ecom company. The amount of catalyst is 0.5g, and the total gas flow rate is set to 800mL / min. The reaction temperature is controlled at 60-320°C through a programmed temperature reactor, and the heating rate is controlled at 2°C / min. The gas flow rates in the flue gas at each temperature point are collected, and the nitrogen oxide conversion rate at the corresponding temperature point is calculated.

[0043] Example 1: The preparation steps of Zr1W1-MnO2 composite metal oxide type denitration catalyst are as follows:

[0044] Preparation of Zr1W1-MnO2: Weigh 7.4g of manganese chloride tetrahydrate (MnCl2·4H2O) and 12.867g of ammonium persulfate ((NH4)2S2O8), add 200mL of water, stir and dissolve, then add 0.1634g of zirconium nitrate pentahydrate (Zr(NO3)2·5H2O) and 0.094g of ammonium metatungstate ((NH4)6H2W 12 O 40 ·xH2O, x is the amount of crystal water) stirred and dissolved, the solution was transferred to a 200mL hydrothermal kettle and reacted at 90°C for 24h to obtain a solid-liquid mixture, cooled to room temperature, filtered, washed, and dried in a 60°C forced air drying oven, and then the obtained precursor was ground into fine powder, transferred to a crucible, placed in a muffle furnace and heated to 320°C at a rate of 2°C / min, and kept at a constant temperature for 4h to obtain a Zr1W1-MnO2 composite metal oxide denitrification catalyst. Wherein, the subscripts 1 and 1 represent the molar fraction ratios of Zr, W and Mn used, respectively.

[0045] The obtained catalyst is pressed into tablets and granulated, and the granulated catalyst of 40-60 mesh is loaded into a fixed bed reactor, and the catalyst activity is evaluated by a fixed bed reaction device. The fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path. The temperature of the reactor is controlled by a program temperature rise, a K-type thermocouple detects and feeds back the temperature signal, an 8mm quartz tube is used as a reaction channel, and quartz wool is a fixed bed layer. The catalyst is fixedly placed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor. The reaction temperature is controlled by controlling the temperature of the reactor. After the gases in each channel are adjusted by a pressure reducing valve and a flowmeter, a mixed gas is formed at a set flow rate, and then passed into a quartz tube. After the mixed gas is catalytically deoxidized by the catalyst, it is discharged, and the inlet and outlet gas concentrations are detected by an EN2-F flue gas analyzer of German ecom company. The amount of catalyst is 0.5g, and the total gas flow rate is set to 1400mL / min. The reaction temperature is controlled at 60-320°C through a programmed temperature reactor, and the heating rate is controlled at 2°C / min. The gas flow rates in the flue gas at each temperature point are collected, and the nitrogen oxide conversion rate at the corresponding temperature point is calculated.

[0046] Example 2: Zr 2.5 W 2.5 The preparation steps of the MnO2 composite metal oxide type denitrification catalyst are as follows:

[0047] Zr 2.5 W 2.5Preparation of -MnO2: Weigh 9.38g of manganese nitrate tetrahydrate (Mn(NO3)2·4H2O) and 17.156g of ammonium persulfate ((NH4)2S2O8), add 180mL of citric acid solution, stir and dissolve, then add 0.227g of zirconium oxynitrate (ZrO(NO3)2·xH2O) and 0.2424g of ammonium metatungstate ((NH4)6H2W 12 O 40 ·xH2O) was stirred and dissolved, and the solution was transferred to a 180mL hydrothermal kettle and reacted at 110°C for 28h to obtain a solid-liquid mixture. After cooling to room temperature, it was filtered, washed, and dried in a blast drying oven at 80°C. The obtained precursor was then ground into fine powder, transferred to a crucible, and placed in a muffle furnace and heated to 360°C at a heating rate of 2°C / min, and kept at this temperature for 6h to obtain Zr 2.5 W 2.5 -MnO2 composite metal oxide type denitrification catalyst, wherein the subscripts 2.5 and 2.5 represent the molar fractions of Zr and W used, respectively.

[0048] The obtained catalyst is pressed into tablets and granulated, and the granulated catalyst of 40-60 mesh is loaded into a fixed bed reactor, and the catalyst activity is evaluated by a fixed bed reaction device. The fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path. The temperature of the reactor is controlled by a program temperature rise, a K-type thermocouple detects and feeds back the temperature signal, an 8mm quartz tube is used as a reaction channel, and quartz wool is a fixed bed layer. The catalyst is fixed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor. The reaction temperature is controlled by controlling the temperature of the reactor. After the gases in each channel are adjusted by a pressure reducing valve and a flowmeter, a mixed gas is formed at a set flow rate, and then passed into a quartz tube. After the mixed gas is catalytically deoxidized by the catalyst, it is discharged, and the inlet and outlet gas concentrations are detected by an EN2-F flue gas analyzer of German ecom company. The amount of catalyst is 0.5g, and the total gas flow rate is set to 1000mL / min. The reaction temperature is controlled at 60-320°C through a programmed temperature reactor, and the heating rate is controlled at 4°C / min. The gas flow rates in the flue gas at each temperature point are collected, and the nitrogen oxide conversion rate at the corresponding temperature point is calculated.

[0049] Example 3: The preparation steps of Zr5W5-MnO2 composite metal oxide type denitration catalyst are as follows:

[0050] Preparation of Zr5W5-MnO2: Weigh 9.16g of manganese acetate tetrahydrate (MnC4H6O4·4H2O) and 21.445g of ammonium persulfate ((NH4)2S2O8), add 160mL of water, stir and dissolve, then add 0.37g of zirconium oxychloride (ZrOCl2·nH2O) and 0.5117g of ammonium metatungstate ((NH4)6H2W 12 O40 ·xH2O) was stirred and dissolved, and the solution was transferred to a 160mL hydrothermal kettle and reacted at 130°C for 32h to obtain a solid-liquid mixture. After cooling to room temperature, it was filtered, washed, and dried in a 100°C forced air drying oven. The obtained precursor was then ground into fine powder, transferred to a crucible, and placed in a muffle furnace and heated to 400°C at a heating rate of 2°C / min, and kept at this temperature for 8h to obtain a Zr5W5-MnO2 composite metal oxide denitrification catalyst. Wherein, the subscripts 5 and 5 represent the molar fractions of Zr and W used, respectively.

[0051] The obtained catalyst is pressed into tablets and granulated, and the granulated catalyst of 40-60 mesh is loaded into a fixed bed reactor, and the catalyst activity is evaluated by a fixed bed reaction device. The fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path. The temperature of the reactor is controlled by a program temperature rise, a K-type thermocouple detects and feeds back the temperature signal, an 8mm quartz tube is used as a reaction channel, and quartz wool is a fixed bed layer. The catalyst is fixed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor. The reaction temperature is controlled by controlling the temperature of the reactor. After the gas of each channel is adjusted by a pressure reducing valve and a flowmeter, a mixed gas is formed at a set flow rate, and then passed into a quartz tube. After the mixed gas is catalytically deoxidized by the catalyst, it is discharged, and the inlet and outlet gas concentrations are detected by an EN2-F flue gas analyzer of German ecom company. The amount of catalyst is 0.5g, and the total gas flow rate is set to 600mL / min. The reaction temperature is controlled at 60-320°C through a programmed temperature reactor, and the heating rate is controlled at 6°C / min. The gas flow rates in the flue gas at each temperature point are collected, and the nitrogen oxide conversion rate at the corresponding temperature point is calculated.

[0052] Example 4: Zr 10 W 10 The preparation steps of the MnO2 composite metal oxide type denitrification catalyst are as follows:

[0053] Zr 10 W 10 Preparation of -MnO2: Weigh 5.91g potassium permanganate (KMnO4) and 8.578g ammonium persulfate ((NH4)2S2O8), add 140mL citric acid solution, stir and dissolve, then add 2.01g zirconium nitrate pentahydrate (Zr(NO3)2·5H2O) and 1.15g ammonium tungstate ((NH4)2S2O8) 10 H2(W2O7)6) was stirred and dissolved, and the solution was transferred to a 140mL hydrothermal kettle and reacted at 150°C for 36h to obtain a solid-liquid mixture. After cooling to room temperature, it was filtered, washed, and dried in a 120°C forced air drying oven. The obtained precursor was then ground into fine powder, transferred to a crucible, and placed in a muffle furnace and heated to 440°C at a rate of 2°C / min, and kept at this temperature for 10h to obtain Zr 10W 10 -MnO2 composite metal oxide type denitration catalyst, wherein the subscripts 10 and 10 represent the molar fractions of Zr and W used, respectively.

[0054] The obtained catalyst is pressed into tablets and granulated, and the 40-60 mesh granulated catalyst is loaded into a fixed bed reactor, and the catalyst activity is evaluated by a fixed bed reaction device. The fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path. The temperature of the reactor is controlled by a program temperature rise, a K-type thermocouple detects and feeds back the temperature signal, an 8mm quartz tube is used as a reaction channel, and quartz wool is a fixed bed layer. The catalyst is fixed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor. The reaction temperature is controlled by controlling the temperature of the reactor. After the gases in each channel are adjusted by a pressure reducing valve and a flowmeter, a mixed gas is formed at a set flow rate, and then passed into a quartz tube. After the mixed gas is catalytically deoxidized by the catalyst, it is discharged, and the inlet and outlet gas concentrations are detected by an EN2-F flue gas analyzer of German ecom company. The amount of catalyst is 0.5g, and the total gas flow rate is set to 1200mL / min. The reaction temperature is controlled at 60-320°C through a programmed temperature reactor, and the heating rate is controlled at 8°C / min. The gas flow rates in the flue gas at each temperature point are collected, and the nitrogen oxide conversion rate at the corresponding temperature point is calculated.

[0055] Catalyst activity using NO x The conversion rate is evaluated by calculating the changes in the concentration components of the inlet and outlet flue gas at each test temperature point, and the concentration change value of the nitrogen oxide gas passing through the catalyst is calculated, and a temperature-concentration curve is drawn. The specific calculation formula is: NO x Conversion rate = ([NO x ] in -[NO x ] out ) / [NO x ] in , where [NO x ] in 、[NO x ] out Represent the fixed bed reactor inlet NO x The concentration and outlet NO x All data are read after the denitrification reaction is stable. x The concentration is read directly on the flue gas analyzer. Figure 1 The NO of the catalysts with different Zr and W contents prepared in Examples 1-5 x Conversion rate diagram. It can be found that MnO2 has better low-temperature catalytic performance, and can reach a conversion rate of 90% at 150°C, while NO xThe operating temperature window for a conversion rate higher than 90% is only 50°C. However, after the introduction of Zr and W elements, the effective operating temperature window of the catalyst is significantly broadened. 2.5 W 2.5 -MnO2 catalyst in the range of 120℃-320℃ x The conversion rate remains above 90%. x There is a volcanic relationship between the conversion rate, the total ratio of the introduced elements and the test gas space velocity. 2.5 W 2.5 -MnO2 and Zr5W5-MnO2 have better overall catalytic activity, W-90(NO x The temperature window with conversion rate higher than 90% reached 200℃. 10 W 10 -MnO2 has a slightly lower catalytic activity at the highest temperature test point, but its test air velocity is higher, reaching 210,000h -1 With 180,000h -1 , and the overall nitrogen oxide conversion rate in the target temperature range (120-320℃) can still be maintained at about 90%. In summary, the synergistic effect between Zr and W promotes the low-temperature NO x The catalytic reduction performance is improved and the operating temperature window of the catalyst is significantly broadened. Moreover, after changing the space velocity of the introduced atmosphere, the overall catalytic effect is maintained at a good level.

[0056] Figure 2 The XRD patterns of the catalysts with different Zr and W contents prepared in Examples 1-5 show that the MnO xThere are obvious characteristic peaks at 22.4°(1 2 0), 34.5°(0 3 1), 37.1°(1 3 1), 38.8°(2 3 0), 42.6°(3 0 0), 56.1°(1 6 0), 57.4°, 65.6°(4 2 1), 68.9°(0 0 3), which are consistent with the characteristic diffraction peaks of the γ-MnO2 (JCPDS NO.14-0644) standard card. When the total amount of Zr and W introduced is 2 mol%, the two diffraction peaks at 2θ = 22.4°(1 2 0) and 34.5°(0 3 1) cannot be observed in the spectrum; when the total amount of Zr and W introduced continues to increase, the characteristic peak at 2θ = 65.6°(4 2 1) also disappears, and the diffraction peak intensities at 2θ = 37.1°(1 3 1), 38.8°(2 3 0) and 42.6°(3 0 0) show a downward trend compared with MnO2, indicating that the doped Zr and W have obtained mixed oxide particles with weaker crystallinity. In addition, when the total doping amount of Zr and W reaches 5 mol%, new characteristic peaks at 2θ = 24.1°(1 1 0) and 30.4°(1 1 1) can be observed. The former corresponds to MnWO4 (JCPDS NO.72-0478), and the latter corresponds to Mn 0.2 Zr 0.8 O 1.8 (JCPDS NO.77-2157). It shows that a new composite metal oxide crystal phase appears in the catalyst. Table 1 lists the evolution rules of the diffraction peaks and grain sizes of the XRD patterns before and after Zr and W doping. The average grain size (D) is calculated based on the (1 6 0) and (1 3 1) diffraction crystal planes according to the Scherrer formula. The results show that the FWHM of the catalyst diffraction peaks gradually increases with the increase of the Zr and W doping amount, and the corresponding average grain size gradually decreases.

[0057] Table 1 XRD Results and Grain Sizes

[0058]

[0059] Figure 3 The N2 physical adsorption and desorption isotherms of the catalysts with different Zr and W contents prepared in Examples 1-5 are shown. It can be seen that the isotherms of all catalyst samples show type-IV isotherms. However, capillary condensation occurs in a specific pressure range (0.4 < P / P0 < 1.0) after the introduction of Zr and W elements, and the required pressure is smaller than that of the carrier (0.8 < P / P0 < 1.0). This is because the introduction of Zr and W blocks the pores and thus leads to a decrease in the catalyst pore size.

[0060] Figure 4The pore size distribution diagram of the catalysts with different Zr and W contents prepared in Examples 1-5 shows that the pores of the carrier MnO2 mainly include mesopores and a small number of macropores, while the main pores of each modified catalyst are mesopores and a small number of micropores, indicating that the Zr and W particles entering the pores change the pore structure.

[0061] Table 2 shows the Brunauer-Emmett-Teller (BET) specific surface area, pore volume and pore size test results of the catalysts of Examples 1-5. It can be seen that the specific surface area of ​​the catalyst first decreases and then increases with the introduction of Zr and W. This is because the specific surface area of ​​the introduced Zr and W element particles decreases when filling the pore structure. With the continuous increase of the element doping amount, it is inferred from the XRD results that Zr, W and MnO2 form a solid solution, and the specific surface area begins to gradually increase. Similarly, the overall pore volume first shows a downward trend due to the blockage of the pores, until the new pores appear to make up for this part of the loss (that is, when the total element doping ratio reaches 5mol%), the total pore volume begins to increase, while the pore size keeps a decreasing trend.

[0062] Compared with the modified denitration catalyst loaded with manganese and cerium on modified biochar of Chinese invention patent application 202410636962.X, which only maintains a conversion rate of more than 90% within the working temperature window of 140-220°C, the ZrW-MnO2 composite metal oxide complex denitration catalyst adopted in the present invention selects Zr and W elements as active components, and increases its working temperature range in both directions by enhancing the reducibility of manganese metal oxide at low temperature and the acidity at high temperature, so that it has a wider low-temperature catalytic working temperature window, covering 120-320°C, and can be applied to a variety of application scenarios in different working temperature zones without replacing the catalyst.

[0063] Compared with the manganese cerium silicon composite metal oxide catalyst acidified by inorganic acid in 500ppm NO, 500ppm NH3 and 50,000h -1 Highly efficient conversion of NO under space velocity conditions x The catalyst of the present invention increases the number of acid sites for NH3 adsorption and changes the properties of NO adsorption sites at high temperature, so that the catalyst can be used at a higher space velocity (150,000h -1 ), greater NO x The catalyst can achieve higher catalytic conversion capacity at a concentration of 1000ppm NO, and after reaching the optimal catalytic efficiency, it can still maintain a high conversion efficiency at a higher temperature. As a result, the catalyst of the present invention can be applied to the treatment environment of flue gas with a higher concentration and more different application scenarios, reducing the cost required for flue gas treatment.

[0064] Table 2 Physical structure properties of catalysts

[0065]

[0066] Compared with the denitration catalyst with high entropy oxide as the active component in the Chinese invention patent CN114308053B, the active component of the catalyst of the present invention is selected mainly from the perspective of oxidizability. On the one hand, the formation of Zr and Mn clusters enhances the reducibility of the catalyst itself and improves its low-temperature catalytic performance. Therefore, the catalyst of the present invention can be applied to a lower temperature processing environment. On the other hand, in view of the strong oxidizability of the active substrate MnO2, in order to increase the high-temperature catalytic conversion efficiency, two metal elements with weaker oxidizability, Zr and W, are selected to reduce the excessive oxidation of the catalyst to NH3 and change the adsorption state of the catalyst to NH3 and NO at high temperature. Within the range of 150°C after reaching the highest conversion rate (100%), the activity only decreases by less than 10%. Finally, the trend of the catalyst activity decline at a higher temperature is curbed, and the overall activity curve tends to be gentle, which is less affected by temperature. When encountering waste gas with a higher temperature, it still has a good treatment effect, and the catalyst treatment efficiency will not be affected by the fluctuation of the waste gas temperature.

[0067] It should be noted that the implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Manganese-based composite zirconium-tungsten oxide denitration catalyst, characterized in that: By Zr a W b -MnO2 precursor is obtained by heat treatment at 300-500°C in air atmosphere; the Zr a W b -MnO2 precursor is prepared by adding soluble manganese salt and ammonium persulfate into a solvent, dissolving them, mixing them, stirring until transparent, then adding soluble zirconium salt and soluble tungsten salt, stirring and dissolving, transferring them to a reactor, and hydrothermally reacting them at 80-120°C for 5-50h, taking them out and cooling them to room temperature, filtering, washing and drying the obtained solid-liquid mixture; wherein a and b represent the molar fractions of Zr and W used, respectively, and the molar ratio of Mn, Zr and W is 1:a:b, and a and b are 1%-10%.

2. The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 1, characterized in that The following steps are involved: 1) After mixing soluble manganese salt and ammonium persulfate, add solvent to dissolve, stir until transparent, then add soluble zirconium salt and soluble tungsten salt, stir to dissolve, transfer to a reactor, hydrothermally react at 80-120° C. for 5-50 hours, take out and cool to room temperature, filter, wash and dry the obtained solid-liquid mixture to obtain a solid precursor; 2) The solid precursor obtained in step 1) is calcined at 300-500° C. to obtain a manganese-based composite zirconium-tungsten oxide denitration catalyst.

3. The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 2, characterized in that: The soluble manganese salt is one or more of manganese sulfate monohydrate, manganese acetate tetrahydrate, manganese nitrate tetrahydrate, manganese chloride tetrahydrate and potassium permanganate; The soluble zirconium salt is one or more of zirconyl chloride, zirconyl nitrate and zirconium nitrate pentahydrate; The soluble tungsten salt is ammonium metatungstate and / or ammonium tungstate.

4. The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 3, characterized in that: The molar ratio of the soluble manganese salt to the soluble zirconium salt is 1:0.01-0.1; the molar ratio of the soluble manganese salt to ammonium persulfate is 1:1-10; the molar ratio of the soluble manganese salt to the soluble tungsten salt is 1:0.0008-0.008; The solvent is deionized water or citric acid solution; the mass ratio of the solvent to the soluble manganese salt is 1:0.03-0.

06.

5. The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 2, characterized in that: The drying is carried out in a blast drying oven or a vacuum drying oven at 60-120° C. for 4-30 hours.

6. The method for preparing the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 2, characterized in that: The calcination time is 1-10h.

7. Use of the manganese-based composite zirconium-tungsten oxide denitration catalyst according to claim 1 in flue gas denitration.

8. The use of the manganese-based composite zirconium-tungsten oxide denitration catalyst in flue gas denitration according to claim 7, characterized in that The steps include: 1) tabletting and granulating the manganese-based composite zirconium-tungsten oxide denitration catalyst; 2) The granulated catalyst obtained in step 1) is fixedly loaded into a fixed bed reactor through quartz wool, and the fixed bed reactor is mainly composed of a quartz tube reactor, a reactor and a gas path; the catalyst is fixedly placed in the quartz tube through quartz wool, and then the quartz tube is placed in the reactor, and the reaction temperature is controlled by controlling the temperature of the reactor, and the flue gas is combined according to the set flow rate and then discharged through the quartz tube, and the flue gas flow rate of each 0.5g catalyst is 600-1400mL / min; 3) The reaction temperature is controlled to be 60-320°C by a programmed temperature reactor.

9. The use of the manganese-based composite zirconium-tungsten oxide denitration catalyst in flue gas denitration according to claim 8, characterized in that: The catalyst granulation mesh number of step 1) is 40-80 mesh; the composition of the flue gas of step 2) is: the concentration ratio of NO to NH3 is 1:1-1.5, the O2 concentration is 2.8-4.5%, and N2 is the balance gas.

10. The use of the manganese-based composite zirconium-tungsten oxide denitration catalyst in flue gas denitration according to claim 8, characterized in that: Step 3) The reaction temperature is programmed to rise from 60°C to 320°C at a rate of 1-10°C / min.

Citation Information

Patent Citations

  • Ferro manganese composite oxides catalyst and preparation method and use thereof

    CN101507928A

  • Method for low-temperature oxidation desulfurization of fuel oil

    CN105112089A

  • Metal pillared montmorillonite supported gamma-MnO2 low-temperature denitration catalyst and preparation method thereof

    CN106423192A

  • W-Mn bimetal oxide composite denitration catalyst as well as preparation method and application thereof

    CN112495372A

  • Catalyst combination method for simultaneously removing CO and NOx

    CN113713608A